THE INFLUENCE OF RISK AVERSION ON BRAND LOYALTY WITH BRAND TRUST AND BRAND AFFECT AS MEDIATING VARIABLES (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
Nowadays, cosmetic products are no longer exclusively designed for women but also for men. This creates opportunities and a conducive environment for the emergence of new companies. With the increasing number of companies in the men’s cosmetic industry today, building brand loyalty is one of the biggest challenges that companies will face. This research aims to explore the relationship between risk aversion and brand loyalty, and test whether this relationship is mediated by brand trust and brand affect in the purchase of cosmetic and body care products by men. The sample selection was done using purposive sampling method with 110 male respondents who are students in Surabaya. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the SmartPLS program. The results showed that risk aversion significantly influences brand trust, brand affect, and brand loyalty. Brand trust and brand affect also significantly influence brand loyalty. By analysing brand loyalty and its influencing variables, companies in the men’s cosmetic and body care industry can understand how to develop it, especially by paying attention to aspects such as risk aversion, brand trust, and brand affect.
Keywords: men; brand; companies; trust; loyalty